Agile Office 365 Successful Project Delivery Practices for an Evolving Platform - Croitoru, Haniel (Apress, 2018)
Plan, deploy, and run Office 365 using an agile project management approach. This soup-to-nuts guide teaches you how to apply agile techniques in order to make your Office 365 implementation a success, even as the Microsoft Office 365 platform continues to evolve and introduce new features. The author's approach to teaching time- and resource-saving concepts mirrors the process a team might typically encounter in delivering software projects. Learning begins with an overview of Office 365 and Agile. From there, you delve into topics correlating to product conception, execution, and deployment. The book wraps up with a comprehensive discussion on how Office 365, straight out of the box, can be used as a tool to manage Office 365 deployments and other types of projects. What You'll Learn: Understand what Office 365 is and why it is the world's most popular online business app Adapt your delivery process to work with Office 365 and its regular update schedule Recognize potential risk areas and develop mitigation strategies Discover the tools that are available to make your life easier Manage the transition from deployment to operations Follow end-to-end guidance packed with useful case studies and tools to make your job easier This book is for project managers, business analysts, IT managers, and other team members involved in managing Office 365 in order to deliver solutions for their organization. While not required, a basic understanding of Agile methodologies and Office 365 is useful. Haniel Croitoru is a seasoned SharePoint and Office 365 consultant and Microsoft Office 365 MVP with more than 15 years of experience in public and private sectors, focusing on SharePoint in the roles of consultant, project manager, business analyst, and trainer. Haniel enjoys sharing his expertise and can be found presenting at many conferences and community events. He holds an MS degree in Computer Science, a Master's Certificate in Project Management, and has been a certified Project Management Professional (PMP) since 2007 and Agile Certified Practitioner since 2013.